2001
DOI: 10.1046/j.1524-4725.2001.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Approaches to Venous Ulcers and Compression

Abstract: Good wound care and compression therapy will heal the majority of small venous ulcers of short duration. For ulcers that are slow to heal, other approaches such as venous surgery and grafting with conventional or bioengineered skin substitutes should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Previous studies have documented such limbs and identified other etiologies. 60,61 These include skin diseases, inflammation, and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented such limbs and identified other etiologies. 60,61 These include skin diseases, inflammation, and malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Each year in the United State alone, there are 70,000 burn injuries [7] and 600,000–1,500,000 venous leg ulcers injuries [8]. The treatment of wounds costs nearly $20 billion annually in the US [9].…”
Section: Woundsmentioning
confidence: 99%
“…Good wound care and compression therapy will heal majority of small venous ulcers of short duration. [1] Goals of compression therapy are ulcer healing, reduction of pain and edema, and prevention of recurrence. [2] Compression is used for VLU and narrows veins and restores valve competence and reduces ambulatory venous pressure, thus reducing venous reflux (VR).…”
Section: Introductionmentioning
confidence: 99%